WARTHOG-HUMAN CONFLICTS IN BORGU SECTOR OF KAINJI LAKE NATIONAL PARK, NIGERIA - Adeola, A. J.; Akande, O. A.; Onihunwa, J. O.; Sulyman, A.; Adeniji, O. A.; Alaifa, P. O. (FUDMA Journal of Sciences, 2022)
This study assessed the impacts of common Warthogs (Phacochoerus africanus) on farm crops around Borgu sector of Kainji Lake National Park, Nigeria. Data was obtained with the aid of structured questionnaire in six communities which were purposively selected (Woro, Kemenji, Worumakoto, Maji, Venira and Kanikoko) and questionnaire was randomly administered to the identified farmers. The sample size was put at one hundred and twenty (120) respondents, of which eighty one (81) questionnaires were retrieved. The demographic characteristics of the respondents indicated that age group 31-40 years recorded the highest (39.5%). The finding further revealed that 64.2% of the respondents are Muslim and 65.4% are married. Also majority of the respondents (53.1%) had stay in the study area between 6-10 years. Majority of the respondents agrees that there is presence of Warthog around their farms. The types of crops cultivated by the respondents are Maize, Guinea corn, Rice etc. Majority of the respondents indicated that they have experience crop raiding by Warthog. Types of crops preferred by Common Warthogs showed that Maize is the most preferred. The season of intense crops raiding is the raining season. The various preventive method used by the respondents to prevent Warthogs crop raiding are watch guarding, scare crow and fire/smoke. The possible solution as suggested on how to prevent Warthog-farmers conflicts are compensation and employment. This study confirms that Warthog has an impact of farm lands in the study area by causing much damage on farmer’s crops.